COMMUNITY STRUCTURE OF GASTROPOD IN THE WATUKARUNG VILLAGE INTERTIDAL ZONE, DISTRICT OF PACITAN, EAST JAVA, INDONESIA - Setyono, Dwi Eny Djoko; Kusuma, Hollanda Arief; Poeteri, Nandike Ayudiah; Bengen, Dietrich G; Kurniawan, Ferry (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2019)
Gastropod is a class of snail with the biggest number of species from the mollusk phylum, since it is able to adapt with any type of habitat. Watukarung Village, which has unique characteristic of its rocky beaches and sand dunes, is one of many habitats of gastropods in the intertidal zone. Thus, a basic information on the structure of the gastropods community in the area is required. Research was conducted in August 2014 in Ngalorombo Beach, Pasir Putih Beach, and Kasap Beach. Systematic sampling was applied using the quadratic plot of 1 x 1 m2, while data analyses comprised of density, Shannon-Wiener index, Eveness index, Simpson index, and correspondence analysis. The gastropods were found in studied areas consist of 8 families, 9 genera, and 13 species. The highest density and the most diverse of the category were in Kasap Beach. Eveness index and Simpson index of the species in the three beaches were in the low category. There was a tendency of the gastropods to live in the habitat made up of coarse sand and stones with good water quality, as shown in the result of the correspondence’s analysis.